Корекція просторової традиційності Чернігова у 1920-х рр. - Непотенко, І. (Сiверянський лiтопис, 2017)
Зміни форм продукування наукового пізнання та моделі його відображення зумовили методологічну поліваріантність та використання міждисциплінарних підходів. Це дало можливість поглянути на міський простір у перехідний період у іншій площині та проаналізувати його не як суб’єкт, а об’єкт дослідження, базуючись на конкретній історичній частині (Дитинці) окремого міста (Чернігова). Изменение форм продуцирования научного познания и модели его отображения обусловили методологическую поливариантность и необходимость использования междисциплинарных подходов. Это дало возможность взглянуть на городское пространство в переходный период в другой плоскости и проанализировать его не как субъект, а объект исследования, базируясь на конкретной исторической части (Детинце) определенного города (Чернигова). 1920s were the period of Soviet power formation. All forms of existence and ways of everyday life have changed. Age-old traditions and behavioral norms were broken. Instead they began to implement the new ones. Besides, the local space was modified too. Even if Soviet policy was similar it had some particular features for each locality. Chernihiv is one of the most historical towns in Ukraine with the huge heritage and great number of architectural monuments. It makes Chernihiv unique among others. Dytynets is the richest historical part of it. There were many buildings of different functions on that territory. In 1920s the occupancy has changed. Some of them were closed, others – transformed. It influenced on the local space and city-dwellers attitude. That’s why the old system was ruined. It was the period of formation of new town’s image and spiritual values of Chernihiv city-dwellers.